Moderating influence of parental engagement on impact of attention span on students’ academic achievement in Senior Secondary School Computer Studies - Adewale Owodunni Saka (Pedagogi: Jurnal Ilmu Pendidikan, 2022)
This study investigated the impacts of attention span and parental engagement on students’ academic achievement in Computer Studies. It also determined the moderating influence of parental engagement on the impact of attention span on learners’ academic achievement. A descriptive research design was adopted. The study population comprised all the SS 2 students offering Computer Studies in public senior secondary schools in Sagamu Local Government Area of Ogun State. Two hundred students were selected randomly from ten randomly selected schools. Attention Span Rating Scale (r=0.78) and Students’ Perceived Parental Engagement Questionnaire (r=0.82), and Computer Studies Achievement Test (r=0.62), were used for data collection. The data collected were analyzed using simple percentages and multiple regression at a 0.05 level of significance. The findings revealed significant impacts of attention span, F(1, 198)= 101.207, p<0.05, and parental engagement, F(1, 198)= 12.346, p<0.05 on students’ academic achievement in Computer Studies. The study also established the joint impact of attention span and parental engagement impacted students’ academic achievement, F(2, 197)= 59.168 p<0.05, but no significant moderating influence of parental engagement on the impact of attention span on students’ academic achievement t(196) = 0.301, p>0.05. It is recommended that teachers adopt active learning strategies for their students. Parents should dissuade their children from the extensive use of mobile technologies, which could dwindle their attention span.